The National Institutes of Health COVID-19 NeuroDatabank and NeuroBiobank: A National Resource for Learning, Discovery, and Progress - Troxel, Andrea B.; Frontera, Jennifer A.; Mendoza-Puccini, Carolina (Frontiers in Neurology, 2021)
Patients suffering from COVID-19 experience a wide range of symptoms and sequelae, including increasingly recognized neurological problems. A concerted effort is necessary to identify and characterize these issues, whether newly appearing as a result of COVID-19 disease or exacerbations of underlying conditions. A national resource to collect information and/or biospecimens regarding neurological complications of COVID-19 offers an opportunity for broad representation, harmonization, and rapid learning, all while ensuring robust protection of confidential information through the use of global unique identifiers to protect patient privacy.